Kajian Penggunaan Profil Pultruded Fiber Reinforced Polymer untuk Jembatan Pejalan Kaki - Muhammad Iqbal (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2022)
The interest in composite materials has increased significantly due to their high strength to weight ratio. Utilization of FRP as construction material is not yet popular in Indonesia as it’s generally used for strengthening structural elements. This study aims to provide a design overview of a hypothetical hollow square profile 150.130.10 on a single span bridge with 12, 16, 20 and 24 meters span length variations. The method refers to the AASHTO design criteria in the form of deflection, vibration, and component allowable stress. The results show that all design criteria on a 12 meters span are fulfilled. Due to insufficient bridge stiffness in 20 and 24 meters span, the vertical fundamental frequency is 4.33 Hz and 3.3 Hz respectively, thus the requirements (> 5Hz) are not fulfilled. In addition, the  FRP profile weak axis critical compressive capacity (68.95 kN) cannot withstand the critical load at spans of 16, 20 and 24 meters (respectively: 97.91 kN; 144.39 kN; 185.36 kN). This study shows that dynamic responses and material characteristics are two factors that may determine pedestrian FRP bridges design.